Pendampingan Penguatan Pemasaran melalui Tiktok Shop sebagai Upaya Meningkatkan Penjualan Produk UMKM - Pusposari, Luthfiya Fathi; Firmantika, Lusty; Hidayat, Imam Wahyu; Saputri, Afif Berlian (Jurnal SOLMA, 2024)
Background: In the 5.0 era, business actors must embrace online marketing media. However, not all people possess the skills to create online marketing, including the UMKM owners in Kampungbaru Sub-village, Malang Regency. The purpose of the activity is aimed at providing education, training and assistance in making TikTok Shop as a means of marketing products to increase sales in the UMKM of Kampungbaru Sub-village. Method: The owners of Kripik and Batik UMKM in Wonosari Sub-village were the subjects of the assistance, which took place in July and August of 2024. Three steps comprised the mentoring method: needs analysis, manufacturing support, and activity evaluation. Results: Through this, Kripik Kabul now has access to new marketing channels through TikTok Shop, its owners can fill out product catalogs, and their understanding and proficiency with social media has grown. Using the TikTok application’s menu, suggestions for more devotion to the use of the TikTok Shop were created. Conclusion: Furthermore, the mentoring process needs to be extended in time, and once the mentoring activities are finished, ongoing evaluation is required.